Exploring entrepreneurial intention among European Union youth by education and employment status - Maria Denisa Vasilescu; Elen-Silvana Crivoi; Andreea-Monica Munteanu (PLoS ONE, 2025)
The relatively high vulnerability of young Europeans in the labour market compared to other age groups has led many to seek alternative employment solutions, such as entrepreneurship. While not a comprehensive solution, entrepreneurial initiatives among youth can offer a valuable opportunity for their integration into stable and decent work. This research uses Flash Eurobarometer 513—Social Entrepreneurship and Youth to explore entrepreneurial intentions among European Union youth. The study’s novelty consists of the division of the target population into four distinct categories based on educational and employment status. The results indicate that EU youth are not a homogeneous group. While the motivation to create their own jobs—is a common feature of all young individuals with entrepreneurial intentions, suggesting a necessity-driven entrepreneurial intention, significant differences emerge among sub-groups. Young people who are only studying exhibit an interest in exploiting business opportunities, highlighting the role of education in fostering opportunity-driven entrepreneurship, while NEETs and employed youth are primarily motivated by better income prospects in the intention to start a business. Additionally, youth engaged in education and those integrated into the labour market are better informed about financing and training opportunities Perceived barriers include a lack of education for NEETs and financial risks for others. Funding preferences also differ: NEETs would rely on personal savings, while those balancing study and work would explore diverse sources, including venture capital and incubator support for starting businesses. Our study enhances the understanding of entrepreneurial intentions among EU young people, offering insights that can guide more effective support strategies for fostering entrepreneurial success.